VALES V: a kinematic analysis of the molecular gas content in H-ATLAS galaxies at z ∼ 0.03–0.35 using ALMA. Issue 2 (20th September 2018) - Molina, J; Ibar, Edo; Villanueva, V; Escala, A; Cheng, C; Baes, M; Messias, H; Yang, C; Bauer, F E; Werf, van der; Leiton, R; Aravena, M; et al.
Abstract: We present Atacama Large Millimeter/submillimeter Array (ALMA) resolved observations of molecular gas in galaxies up to $z$ = 0.35 to characterize the role of global galactic dynamics on the global interstellar medium properties. These observations consist of a sub-sample of 39 galaxies taken from the Valparaíso ALMA Line Emission Survey (VALES). From the CO( J = 1–0) emission line, we quantify the kinematic parameters by modelling the velocity fields. We find that the infrared (IR) luminosity increases with the rotational to dispersion velocity ratio ( V rot /σ$v$, corrected for inclination). We find a dependence between V rot /σ$v$ and the [C ii ]/IR ratio, suggesting that the so-called [C ii ] deficit is related to the dynamical state of the galaxies. We find that global pressure support is needed to reconcile the dynamical mass estimates with the stellar masses in our systems with low V rot /σ$v$ values. The star formation rate (SFR) is weakly correlated with the molecular gas fraction ($f_{\rm H_2}$ ) in our sample, suggesting that the release of gravitational energy from cold gas may not be the main energy source of the turbulent motions seen in the VALES galaxies. By defining a proxy of the 'star formation efficiency' (SFE) parameter as the SFR divided by the CO luminosity (SFE′ ≡ SFR/ L $^{′ }_{\rm CO}$ ), we find a constant SFE′ per crossing time ( t cross ). We suggest that t cross may be the controlling time-scale in which the star formation occurs in dusty $z$ ∼ 0.03–0.35 galaxies.